Reconstruction of a chamber furnace - Radchenko, Yu.M.; Gupalo , O.V.; Yeromin , O.O.; Gres , L.P.; Shtatskyi , M.O. (Theory and Practice of Metallurgy, 2024)
Objective. The paper considers the issue of a chamber furnace reconstruction for improving of their energy efficiency. Methods. The chamber furnace is heated by natural gas and operates at a constant temperature in its working chamber. The nominal capacity of the furnace is 100 kg/h. According to the design, the furnace walls are two-layered: the refractory layer made of chamotte (B class) is 120 mm, and the heat-insulating layer made of diatomite bricks is 60 mm. To study the temperature fields and heat losses through the lining during the operation of the furnace, the authors developed a two-dimensional mathematical model of heat conduction through a flat wall for an unsteady-state temperature condition. Findings. Using the mathematical model, numerical calculations were performed for the furnace of the basic design. It was considered three variants of the furnace lining reconstruction. Three variants of the furnace lining reconstruction were considered, which involved replacing the furnace brick lining with a lining made of ceramic fibre (MKRV-340), whose thickness was 180, 120, and 60 mm according to the number of the reconstruction opinion. As the results of the calculation are the heat losses of lining and the temperature distribution in the lining were determined. That made possible to assess the fuel consumptions which covered heat losses and the fuel costs as well as the weight and cost of the lining. The scientific novelty of the work is in the revealed relationship between the design and operational parameters of the furnace, and the practical value of the work is in the developed recommendations for choosing a rational thickness of the furnace lining layer of the ceramic fibre, depending on the expected operation life of the furnace.